Pengaruh Green Accounting dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Cahyaningrum Istiqomah; Winarsih Winarsih (Jurnal Akuntansi Indonesia, 2024)
The influence of Green Accounting and Profitability is an observation that is still rarely used to support the realization of good company value. One observation regarding Green Accounting with a qualitative description measurement procedure shows that the company describes the cost of living nature at its own discretion and is disclosed voluntarily because PSAK does not have specific regulations regarding the disclosure of living nature costs in financial statements. This observation intends to determine the influence of green accounting and profitability on company value in manufacturing companies listed on the Indonesia Stock Exchange. The observation period used was 2018-2020. Based on the Purposive sampling technique, 93 data were obtained. The analysis technique used in this observation is multiple linear regression analysis using IBM SPSS 22. Observation results show that green accounting has a relevant positive effect on company value, profitability has a relevant positive effect on company value.